Organización y archivo de la información de los expedientes estudiantiles de la carrera de ingeniería en contabilidad y auditoría de la unidad académica de ciencias administrativas y humanísticas de la universidad técnica de Cotopaxi en el período 2008-2011 - Chiluisa Quintana, Luis Rodrigo (2014)
The present investigative work is a proposal for the guidelines of a model of organization of the documental series of student leaves of life, of the students of the Technical University of Cotopaxi in the Academic Unit of Administrative and Humanistic Sciences in the Career of Accounting and Audit based mainly on the requirements of the General Law of Files and the politicians of information of the institution. The rules of documental organization look for to solve the organizational holes that impact in a centralized file of the diverse careers, through the application of processes archivísticos besides knowing the covenants of title of the protection of the personal data of the students that you/they rest in the leaves of the students' endowed with an administrative, fiscal, legal value life and technician. These administrative files evidence the execution of the functions of the institutional administration.